Pemakaian Duddingtonia flagrans dan Saccharomyces cerevisiae dalam Mereduksi Larva Infektif Haemonchus contortus (THE STUDY OF DUDDINGTONIA FLAGRANS AND SACCHAROMYCES CEREVISIAE USE ON REDUCING OF INFECTIVE HAEMONCHUS CONTORTUS LARVAE) - Ahmad, Riza Zainuddin; Satrija, Fadjar; Sukarno, Nampiah; Pasaribu, Fachriyan Hasmi (Jurnal Veteriner; Vol 13 No 1 (2012), 2012)
The use of Duddingtonia flagrans as the biological control of nomatode infections has been widelyreported. However, no report is available on the use of yeast Saccharomyces cerviciacae for such purpose.The aim of this study was to ivestigate the use of both fungi to reduce the number of Heamoncus contortusinfective larvae. Agar and fecal media containing the spore of the fungi was inoculated with infected H.contortus larvae (3rd stage). Fecal media containing the fungi was prepared by oral inoculation of sheepwith liquid containing 106, 107 spores of D. flagrans, and 106, 107 spores of D. flagrans, and 106, 1012 sporesof S. cerviciae. The number of larvae trapped in the fungi was counted. The result showed both fungi wereable to reduce the number of infective lave. However, for D. flagrans, beside it able to kill the larvae, it alsoable to trap the larva which did not occur in S. cerviceae. The combination of both fungi can be used to reduceof the number of invected H. contortus larvae.
Keywords: D.flagrans, S. cerevisiae, H. contortus, reduce